2007
DOI: 10.1002/app.27195
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of alkyd resin from jatropha and rapeseed oils and their applications in electrical insulation

Abstract: Alkyd Resin based on Jatropha and Rapeseed oils using glycerol, phthalic, and maleic anhydride were synthesized to obtain the resins suitable for electrical applications. These resins were characterized for the physical and electrical properties. Varnishes were prepared using these resins and characterized as per standard methods. In general, both the varnishes prepared from alkyd resin from jatropha and rapeseed oils meet the standard requirements. However, the varnish prepared from rapeseed oil was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…For example, biodiesel production generates fruit husk that can be used as feedstock for open-core downdraught gasifiers (Vyas and Singh, 2007) for wood gas. Singh et al (2008) reported on using combustion, gasification and oil and biodiesel extraction from J. curcas husk, shells and seeds for a holistic approach to optimal utilization of all parts of the fruits towards obtaining maximum possible energy. Recently, Sricharoenchaikul et al (2008) demonstrated that J. curcas waste pyrolysed at 800°C followed by potassium hydroxide (KOH) activation could generate a low-cost-activated carbon as adsorbent with desirable surface properties for application in various industries.…”
Section: Potential J Curcas Co-productsmentioning
confidence: 99%
“…For example, biodiesel production generates fruit husk that can be used as feedstock for open-core downdraught gasifiers (Vyas and Singh, 2007) for wood gas. Singh et al (2008) reported on using combustion, gasification and oil and biodiesel extraction from J. curcas husk, shells and seeds for a holistic approach to optimal utilization of all parts of the fruits towards obtaining maximum possible energy. Recently, Sricharoenchaikul et al (2008) demonstrated that J. curcas waste pyrolysed at 800°C followed by potassium hydroxide (KOH) activation could generate a low-cost-activated carbon as adsorbent with desirable surface properties for application in various industries.…”
Section: Potential J Curcas Co-productsmentioning
confidence: 99%
“…Palm [16], soybean [14,15,17], tung [16], rapeseed [18], jatropha [18], castor [15], rubber seed [19], melon seed [19], mahua [20] and Nahar seed [21,22] oils have been used as raw materials to prepare monoglycerides via alcoholysis process. In most cases, the vegetable oil based monoglycerides are further modified with different anhydride (glutaric, phthalic, maleic and succinic anhydrides), followed by polycondensation to form various alkyd resins.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous vegetable oils like sunflower, coconut soybean, linseed and castor have been extensively used for the syntheses low molecular weight polymers [14][15][16][17] . However, among these vegetable oils some are edible and other are also poses some medicinal values 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous vegetable oils like sunflower, coconut soybean, linseed and castor have been extensively used for the syntheses low molecular weight polymers [14][15][16][17] . However, among these vegetable oils some are edible and other are also poses some medicinal values 17 . Therefore, it is required to explore the nature's blessings and utilized the non-edible and non-traditional seed oils in making value added polymeric materials which ultimately provide suitable utilization to them as well as reduce the pressure on traditional vegetable oils.…”
Section: Introductionmentioning
confidence: 99%